"Sell when the violins are playing - by when the cannons rumble" - Bazdan, Zdravko (Naše gospodarstvo, 2010)
The focus of this analysis is the answer to the following question: how to choose between two main strategies in order to optimally manage money on the stock exchange. The first group of analytics prefer fundamental approach and second group prefers technical analysis. The philosophy of fundamental analytics is to take into consideration economic climate in the country where the stocks are traded as well as global relationships that can create fluctuation of the stock value for the company in question. The second group of analytics, called technical analytics or chartists base their strategies upon action on the stock market and investor's demand. Knowing how to read the stock tables, and understanding the investment quotes are essential for investment success.
Keywords: finančni trg; borze; borzništvo; Das Kapital; kapital; delnice; management; upravljanje